Students’ perceptions of how English songs improve their listening skills - Jeklin Souhuwat; Virginia Gabrella Sengkey (Institute of Computer Science (IOCS), 2023)
This study aimed to discover students' perception of how English songs improve their listening skills. Also, this study wanted to investigate whether there is significant difference on students’ perception of how English songs improve their listening skills based on gender. The methods used in this research was descriptive and comparative. The instrument used in this study was a questionnaire adapted from Ngoc (2021). This research was conducted to the eleventh-grade students enrolled in the first semester of the 2022/2023 academic year at a private high school in North Minahasa. The results were: (1) the students agreed on the reasons and principles of using English songs in improving their listening skills; (2) they also agreed that English songs were a good learning resource to help them improve their listening skills (3); students also agreed that English songs play an important role in learning listening; (4) however, there was no significant difference on students' perception of how English songs improve their listening skills based on gender. Thus, this research recommended that (a) using English songs in class should be an option for teachers in teaching, especially in teaching English; (b) also, further research needs to be conducted to see other factors that can significantly affect students’ listening skills.